Non-canonical DNA structures: Diversity and disease association - Bansal, Aparna; Kaushik, Shikha; Kukreti, Shrikant (Frontiers in Genetics, 2022)
The importance and the significance of DNA as the genetic material can be appreciated from a complete understanding of its double-helical structure, discovered by James Watson and Francis Crick in 1953. For the last seven decades, this has been a leading light in the course of the development of modern biology and biomedical science. In addition to the predominant canonical B-form right-handed double helix, experimental shreds of evidence have revealed the existence of a sequence-dependent structural diversity, unusual non-canonical structures like hairpin, cruciform, Z-DNA, and multistranded triplex, G-quadruplex i-motif forms, etc. The diversity in the DNA structure depends on various factors such as base sequence, ions, superhelical stress, ligands, etc. In response to these various factors, the polymorphism of DNA plays a crucial role in various biological processes like replication, recombination, and transcription, by interacting with the regulatory region of the gene or proteins. However, altered levels of gene expression are associated with many human genetic diseases including neurological disorders and cancer. These non-B-DNA structures have an impact on DNA damage, repair, and genetic stability. The present review is a modest attempt to summarize the available literature illustrating the occurrence of non-canonical structures at the molecular level in response to the environment, and interaction with ligands and proteins. This would provide an insight to understand the biological functions of these unusual DNA structures and their recognition as potential therapeutic targets for diverse genetic diseases.